Implementation Development Of Work Climate To Better Worker Productivity Employee In Stikes Hang Tuah Surabaya - Dedi Irawandi (Journal of Global Pharma Technology, 2020)
Productive nurses are produced from qualified educational institutions. To achieve optimal work productivity growth required several supporting factors, one of them is the harmonious working climate. This work purports to obtain a photo of the workplace climate and its relationship to employee productivity. The dimensions of the employment climate in search are (1) the concept of the psychological dimension of employees; (2) the structural proportions of employees; (3) social dimensions of employees; (4) employee bureaucratic dimension. This research uses a quantitative and qualitative approach. The Result of research (1) Worker productivity at Stikes Hang Tuah Surabaya shows good work productivity (58%), unfavorable (42%), (2) Psychological dimension related to work productivity; (3) Structural dimension is not related to work productivity; (4) Social dimension related to work productivity; (5) The bureaucratic dimension is not related to work productivity. Recommendations for the management, need to be developed further standard performance of a team sharing development and application of a fair reward system for the achievers and penalties for the violators